2007
DOI: 10.4049/jimmunol.179.10.6783
|View full text |Cite
|
Sign up to set email alerts
|

Localization and Differential Expression of Activation-Induced Cytidine Deaminase in the Amphibian Xenopus upon Antigen Stimulation and during Early Development

Abstract: As in mammals, B cell maturation in the amphibian Xenopus involves somatic hypermutation (SHM) and class switch recombination to diversify the B cell receptor repertoire in response to Ag stimulation. Unlike mammals, however, the resulting increase in Ab affinity is poor in Xenopus, which is possibly related to the absence of germinal centers and a suboptimal selection mechanism of SHM. In mammals, both SHM and class switch recombination are mediated by the activation-induced cytidine deaminase enzyme and unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 47 publications
2
50
0
Order By: Relevance
“…The increase in IgM ϩ B cells at 6 dpi is interesting since we have reported that some B cells proliferate in the spleen during FV3 infection (24,31) and that activated B cells expressing activation-induced cytidine deaminase are present in the periphery (26). The drop in T-cell numbers at 3 dpi, on the other hand, is intriguing.…”
Section: Discussionmentioning
confidence: 91%
“…The increase in IgM ϩ B cells at 6 dpi is interesting since we have reported that some B cells proliferate in the spleen during FV3 infection (24,31) and that activated B cells expressing activation-induced cytidine deaminase are present in the periphery (26). The drop in T-cell numbers at 3 dpi, on the other hand, is intriguing.…”
Section: Discussionmentioning
confidence: 91%
“…Further suggestions of functions for AID beyond the immune system come from studies of lower vertebrates. As in mice, AID is expressed during early development in Danio rerio (Rai et al 2008), Xenopus laevis (Marr et al 2007), and the newt Pleurodeles waltl (Bascove and Frippiat 2010). The broad conservation of this pattern of AID expression strongly suggests a function in early development.…”
Section: Aid Beyond the Immune Systemmentioning
confidence: 89%
“…We show here that AID induced by NP-Ficoll is expressed at lower levels than in GC blasts and is not coexpressed with Bcl6. Germinal center independent class switching may represent an ancient pathway of AID induction that developed before proper germinal centers evolved, as is seen in lower vertebrates that develop plasma cells and undergo CSR in the absence of germinal centers [24]. CSR occurring before affinity maturation happens may seem counterproductive, as a switch from IgM to IgG leads to a loss of avidity of the resulting antibody.…”
Section: Discussionmentioning
confidence: 99%